STROKE PREVENTION EDUCATION AND POST-STROKE CARE, AND EXPLORATION OF GENETIC PROFILES - Arisetijono, Eko; Yueniwati, Yuyun; Setianto , Catur Ari; Prabowo , Bisma Dewanto Ari; Ernanda , Shelby Amrus; Agustin , Aisyiyah Alviana; Gumelar , Enggar; Hasibuan , Muhammad Effendy Nugraha; Irnanda , Miranthi Ayu; Azzakiy , Ahmad Abdul Hadiy; Riandono , Dody; Ibrahim , Ananto Suar Bhakti; Pratama , Senoadji; Friscillia , Febrina; Muhammad , Galang Mahasin; Aprilianingtyas , Arvidareyna Panca; Putri , Firda Aunidiah; Rahmaditta , Allyssa; Purnama , Sari Dianita; Maliga , Helnida Anggun (MNJ (Malang Neurology Journal), 2026)
Background: Stroke is a leading cause of disability and mortality in Indonesia, making prevention and post-stroke care crucial to improving patients' quality of life. Objective: This community service project aimed to provide education on stroke prevention and post-stroke care in Besole Village, introduce a stroke risk screening application called Sinarsis (https://sinarsis.id), and explore genetic risk profiles for stroke in one participant. Methods: The method employed was a classical educational approach, encompassing explanations of stroke, prevention strategies, and post-stroke care by family members. Participants were also introduced to the Sinarsis application as a stroke risk screening tool. Results: Out of 51 participants, evaluation results indicated that 80% rated the program as highly beneficial, while 20% found it beneficial. Additionally, 90% of participants strongly agreed that similar programs should be conducted in the future. Regarding perceived knowledge gain, 86% of participants reported acquiring new insights on stroke, and 90% reported feeling highly motivated to prevent stroke. Furthermore, 84% of participants with family members who had experienced a stroke reported feeling highly motivated to improve post-stroke care. A genetic risk profile examination was conducted on one participant for further exploration of stroke risk, though it was limited to a single individual due to constraints on testing kits and funding. Conclusion: In conclusion, this educational program effectively enhanced knowledge and motivation among Besole Village residents regarding stroke prevention and post-stroke care. The Sinarsis application is anticipated to serve as a valuable tool for community-based stroke risk screening.